Surprise island - Warner, Gertrude Chandler, 1890-1979 (Warner, Gertrude Chandler, 1890-1979. Boxcar children mysteries, 2023)
Spending the summer on Grandfather's island turns out to be more of an adventure than Henry, Jessie, Violet, and Benny Alden could ever expect.